2018
DOI: 10.1038/s41598-018-23838-w
|View full text |Cite
|
Sign up to set email alerts
|

Causal Inference in the Perception of Verticality

Abstract: The perceptual upright is thought to be constructed by the central nervous system (CNS) as a vector sum; by combining estimates on the upright provided by the visual system and the body’s inertial sensors with prior knowledge that upright is usually above the head. Recent findings furthermore show that the weighting of the respective sensory signals is proportional to their reliability, consistent with a Bayesian interpretation of a vector sum (Forced Fusion, FF). However, violations of FF have also been repor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 42 publications
5
45
0
Order By: Relevance
“…This variability could be interpreted as a sign that individuals are wired differently with respect to processes governing the formation of perceptions. However, we believe this to be unlikely: a similar variability has been reported in recent studies on the applicability of CI for perception of heading [20,21] and verticality [22]. As in the present study, it was found that different models were preferred over CI in individual cases, although in these studies the FF model was preferred in the majority of cases.…”
Section: Multisensory Distance Estimationsupporting
confidence: 87%
See 4 more Smart Citations
“…This variability could be interpreted as a sign that individuals are wired differently with respect to processes governing the formation of perceptions. However, we believe this to be unlikely: a similar variability has been reported in recent studies on the applicability of CI for perception of heading [20,21] and verticality [22]. As in the present study, it was found that different models were preferred over CI in individual cases, although in these studies the FF model was preferred in the majority of cases.…”
Section: Multisensory Distance Estimationsupporting
confidence: 87%
“…This formulation reflects the Model Averaging CI strategy (e.g., [18,28,29]). It is similar to earlier work by our group on heading estimation [20,30,21] and the perception of verticality [22]. The probability of a common cause given the sensory estimates is .…”
Section: Causal Inference Modelsupporting
confidence: 85%
See 3 more Smart Citations